ENHANCING STUDENTS’ ENGLISH LANGUAGE LEARNING THROUGH LINGUA-DIDACTICS IN THE CREDIT-MODULE SYSTEM OF HIGHER EDUCATION - Khaknazarova, Luiza; Narmatova, Manzura; Khaydarova, Shoira; Jonuzakova, Kamola; Normatov, Rikhsimurod; Joldasova, Gozzal; Маtberdieva, Yulduz; Rustamov, Ilkhom; Sindorov, Lutfulla; Khusanova, Shokhsanam; Avazov, Normurod (Veredas do Direito, 2025)
This study investigates how integrating lingua-didactic principles into the credit-module system can enhance English language learning in higher education. As universities shift toward more student-centered and flexible academic models, there is a growing need for teaching strategies that promote autonomous learning, communicative competence, and overall academic achievement. The research focuses on the application of lingua-didactic methods such as blended learning, task-based instruction, and digital integration and examines how these approaches align with the structure of modular education. A mixed-methods approach was used, including a survey of 120 students and in-depth interviews with 20 English language instructors. The findings reveal that incorporating lingua-didactic strategies leads to improved learner engagement, stronger vocabulary development, and increased confidence in language use. Based on the results, the study recommends institutionalizing lingua-didactic training for educators and expanding access to digital instructional tools within modular frameworks.